Metabolic Syndrome and Antipsychotics: The Role of Mitochondrial Fission/Fusion Imbalance - del Campo, Andrea; Bustos, Catalina; Mascayano, Carolina; Acuña-Castillo, Claudio; Troncoso, Rodrigo; Rojo, Leonel E. (Frontiers in Endocrinology, 2018)
Second generation antipsychotics (SGAs) are known to increase cardiovascular risk through several physiological mechanisms, including insulin resistance, hepatic steatosis, hyperphagia and accelerated weight gain. There are limited prophylactic interventions to prevent these side effects of SGAs, in part because the molecular mechanisms underlying SGAs toxicity are not yet completely elucidated. In this perspective article we introduce an innovative approach to study the metabolic side effects of antipsychotics through the alterations of the mitochondrial dynamics, which leads to an imbalance in mitochondrial fusion/fission ratio and to an inefficient mitochondrial phenotype of muscle cells. We believe that this approach may offer a valuable path to explain SGAs-induced alterations in metabolic homeostasis